Identification of models, theoretical design and formal evaluation of integrated specialist community health service provision for the first 2000 days: a protocol for a scoping review - Nelson, Helen Jean; Munns, Ailsa; Ong, Sarah; Watson, Leanne; Burns, Sharyn (BMJ open, 2022)
IntroductionThe first 2000 days of a child’s life (during pregnancy up to age 5 years) represent a critical period, in which early interventions reduce risk associated with developmental delay, disability and intergenerational disadvantage. The risk is exacerbated by barriers to specialised early intervention for children and families. This scoping review seeks to contribute to the evidence for sustaining integrated community-based specialist care in these earliest years of a child’s life.Methods and analysisThe Joanna Briggs Institute scoping review framework will be followed. Inclusion and exclusion criteria for screening of literature is predefined, guided by the criteria of population, concept and context. The review will identify models of care delivery, and will identify quality of care outcomes that have been measured, including evidence of reliability and validity. Sources of evidence will include CINAHL, Cochrane databases, Medline, PsycINFO and Scopus.Ethics and disseminationIn a three-part study, evidence synthesis from the scoping review of the literature; mapping of existing specialist early years services in one community and a consumer consultation (Curtin University Human Research Ethics approval HRE2021-0546) in the same community will inform a model of integrated care that accounts for the context of the community it seeks to serve. Results will be disseminated by peer-reviewed publications and conference presentations, contributing to the evidence base for delivering sustainable community-based integrated care in the context of the first 2000 days. This protocol is specific to the scoping review.